Analisis Strategi Pemasaran Pada UMKM Nawasena Dalam Meningkatkan Minat Beli Konsumen - Eva Yunita Sari; Hartono Hartono; Rini Armin (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
This thesis discusses the Analysis of Marketing Strategies in Nawasena Efforts to Increase Consumer Buying Interest. In this study raised issues in the form of: influencing factors in the development of SMEs and marketing strategies of SMEs. This study aims: to determine the factors that influence the marketing strategy of SMEs. This research method is a qualitative approach using descriptive analysis method on 4 respondents, namely business owners and 3 employees. The data was collected by means of observation, interviews, questionnaires filled in by respondents, as well as documentation. Then the data obtained from the results of data collection were analyzed using SWOT, IFAS and EFAS analysis.